2007
DOI: 10.1007/s12070-007-0027-0
|View full text |Cite
|
Sign up to set email alerts
|

Lipoma of tongue — A rare site for a rare site for a common tumour

Abstract: Lipoma is the commonest benign tumour occurring at any anatomical site where fat is present. In oral cavity and oropharynx it is a relatively uncommon neoplasm.. Tongue which is totally devoid of fat cells is also a site for lipoma albeit very rarely. This is one such rare case of the universal tumour, presenting at the lateral margin of the tongue, for which complete tumour excision was done.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 4 publications
0
15
0
3
Order By: Relevance
“…Oral lipomas may occur on the major salivary glands, buccal mucosa, lip, palate, vestibule, floor of the mouth and tongue (21). Tongue lipomas are relatively rare and usually arise in the superficial submucosal connective tissue (22). The present study compared the characteristics of 18 cases of tongue lipoma reported in China over a 30-year period.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Oral lipomas may occur on the major salivary glands, buccal mucosa, lip, palate, vestibule, floor of the mouth and tongue (21). Tongue lipomas are relatively rare and usually arise in the superficial submucosal connective tissue (22). The present study compared the characteristics of 18 cases of tongue lipoma reported in China over a 30-year period.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathologically benign lipomas are classified as: Lipoma or classical lipoma; lipoma variants, including angiolipoma, angiomyolipoma, myolipoma, fibrolipoma, chondroid lipoma, chondrolipoma, osteolipoma, intramuscular lipoma, myelolipoma, sialolipoma and spindle cell/pleomorphic lipoma; hemartomatous lesions; diffuse lipomatous proliferations; and hibernoma (21)(22)(23). Lipomas may be encapsulated, non-encapsulated or infiltrating (21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lipoblastic embryonic cell nest origin, hormonal cause, infection, fat degeneration, hereditary and chronic irritation have also been attributed [13] .…”
Section: Discussionmentioning
confidence: 99%